2005
DOI: 10.1007/s00436-005-1364-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations of the dihydrofolate reductase gene of Plasmodium vivax in Mandalay Division, Myanmar

Abstract: Dihydrofolate reductase (DHFR; EC1.5.1.3) is a known target enzyme for antifolate agents, which are used as alternative chemotherapeutics for chloroquine-resistant malaria. Mutations in the dhfr gene of Plasmodium vivax are thought to be associated with resistance to the antifolate drugs. In this study, we have analyzed genetic variations in the dhfr genes of clinical isolates of P. vivax (n=21) in Myanmar, to monitor antifolate resistance in this country. Sequence variations within the entire dhfr gene were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
5
23
1
Order By: Relevance
“…Because this mutation occurs at a high frequency (9.1%), the characteristics of this residue warrant further study. Regarding the combinations of mutations in pvdhfr , the observations that mutation 117N was not observed in the pvdhfr quadruple mutants in this study, although the quadruple mutants always included the mutation 117N/T in previous studies, 5,11 and that mutation 61M was only seen in the quadruple mutants, are consistent with previous data. 26 However, the observation that 57L was not linked to 58R, but occurred alone in a small percentage of isolates from Korea (22.7%), is inconsistent with the results of a previous study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Because this mutation occurs at a high frequency (9.1%), the characteristics of this residue warrant further study. Regarding the combinations of mutations in pvdhfr , the observations that mutation 117N was not observed in the pvdhfr quadruple mutants in this study, although the quadruple mutants always included the mutation 117N/T in previous studies, 5,11 and that mutation 61M was only seen in the quadruple mutants, are consistent with previous data. 26 However, the observation that 57L was not linked to 58R, but occurred alone in a small percentage of isolates from Korea (22.7%), is inconsistent with the results of a previous study.…”
Section: Discussionsupporting
confidence: 92%
“…22 However, in 1999 (this study), 7 of 14 isolates were double mutants, 3 of 14 isolates were quadruple mutants, and 3 isolates carried only wild-type alleles; there were no triple mutants. In contrast, in 2005, 9 of 21 isolates were double mutants and 8 were quadruple mutants, 11 which indicated that these mutations may increase rapidly in isolates with highly mutated pvdhfr alleles. Therefore, the thorough and frequent surveillance of SNPs of drug-resistance genes is useful and important in monitoring drug resistance in malaria-endemic countries.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The pvdhfr gene was amplified using the primer 5′-ATGGAGGACCTTTCAGATGTA TTTGACATT-3′ and 5′-CTTGCTGTAAACCAAAAAGTC CAGAGTGGT-3′ as described. 34 The PCR was performed with the following parameters: 94°C for 5 minutes; fol lowed by 30 cycles at 94°C for 20 seconds, 60°C for 30 seconds, and 72°C for 1 minute; and a final elongation at 72°C 10 minutes. The pvdhps gene was ampli fied by nested PCR with the outer primers (forward 5′-TTGAAACACGCATTATGGTATCG-3′ and reverse 5′-AAGCGTAGCGACAGAAGAACG-3′) and inner primers (forward 5′-GAGATTACCCTAAGGTTGAT GTATC-3′ and reverse 5′-GGTTTATTTGTCGATCCTGT G-3′).…”
Section: Samplementioning
confidence: 99%
“…2017; 10(9):e57697. 5 resistance in P. falciparum, quadruple mutant alleles of pvdhfr at codons 57, 58, 61, and 117 were predominated in clinical isolates from India, Myanmar, Indonesia (28)(29)(30), and Thailand (31). It appears that in these countries, diversity in the frequency of mutant pvdhfr alleles is a sign of drug pressure by usage of anti-folates.…”
Section: Discussionmentioning
confidence: 99%